A needle in a haystack: Endoscopic removal of a foreign body from the infratemporal fossa. (April 2018) - Ioanidis, Khrystyna; Rotenberg, Brian
Background: This report presented the case of a difficult-to-remove needle foreign body. The patient had a dental procedure in which a 30-gauge needle was lost in the gingival buccal sulcus. Several attempts at removal were unsuccessful. The patient presented to the otolaryngology clinic with trismus, pain with mastication, intermittent right otalgia, and numbness of the right cheek. Methods: The needle was finally localized in the infratemporal fossa and removed by using image guidance technology. Results: This case demonstrated an approach to a difficult-to-locate foreign body removal and the importance of intraoperative imaging in foreign body localization. Conclusion: Foreign bodies of the infratemporal fossa and posterior orbit are better removed via endoscopic than open technique.